Because of Winn-Dixie [videorecording (Blu-Ray)] - Albert, Trevor; Singleton, Joan; Wang, Wayne, 1949-; Daniels, Jeff, 1955-; Tyson, Cicely; Matthews, Dave, 1967-; Saint, Eva Marie, 1924-; Robb, AnnaSophia, 1993- (20th Century Fox Home Entertainment, 2011)
The heartwarming 'tail' of a young girl whose life is changed by a scruffy, fun-loving pooch she names Winn-Dixie. The special bond between them works magic on her reserved dad and the eccentric townspeople they meet during one unforgettable summer.